Hemoglobin Is a Vital Determinant of Arterial Oxygen Content in Hypoxemic Patients with Pulmonary Arteriovenous Malformations. - Rizvi,A; Macedo,P; Babawale,L; Tighe,HC; Hughes,JM; Jackson,JE; Shovlin,CL (Annals of the American Thoracic Society, 2017)
RATIONALE: Arterial partial pressure of oxygen (PaO2), and oxygen saturation (SaO2) are commonly measured in respiratory practice, but arterial oxygen content (CaO2) refers to the volume of oxygen delivered to the tissues per unit blood volume. CaO2 is calculated from SaO2 and the hemoglobin concentration in blood, recognizing that each gram of hemoglobin can transport approximately 1.34mls of oxygen when fully saturated. OBJECTIVES: To prospectively evaluate serial changes in CaO2 in man, incorporating and excluding dynamic changes to oxygenation and hemoglobin parameters that may occur during life. METHODS: A cohort of 497 consecutive patients at risk of both hypoxemia and anemia were recruited. The patients had radiologically-proven pulmonary arteriovenous malformations (PAVMs) which result in hypoxemia due to right-to-left shunting, and concurrent hereditary hemorrhagic telangiectasia (HHT) which placed them at risk of iron deficiency anemia due to recurrent hemorrhagic iron losses. Presentation SaO2 (breathing room air, by pulse oximetry), hemoglobin, red cell and iron indices were measured, and CaO2 calculated by SaO2hemoglobin1.34mls/gram. Serial measurements were evaluated in 100 cases spanning up to 32.1 (median 10.5) years. RESULTS: Presentation CaO2 ranged from 7.6-27.5 (median 17.6) mls/dL. CaO2 did not change appreciably across the SaO2 quartiles. In contrast, hemoglobin ranged from 5.9-21.8g/dL (median 14.1g/dL), with a linear increase in CaO2 across hemoglobin quartiles. Following PAVM embolization and an immediate increase in SaO2, hemoglobin fell and CaO2 was unchanged 1.6-12 (median 4) months later. When hemoglobin fell due to iron deficiency, there was no change in SaO2. Similarly, when hemoglobin rose after iron treatment, there was no change in SaO2, and the expected CaO2 increment was observed. These relationships were not evident during pregnancy when hemoglobin fell, and PAVMs usually deteriorated: In pregnancy SaO2 commonly increased, and